Laser-activated transforming growth factor-[beta]1 induces human [beta]-defensin 2: implications for laser therapies for periodontitis and peri-implantitis - Tang, E; Khan, I; Andreana, S; Arany, P R (Journal of periodontal research, 2017)
Background There is increasing popularity of high-power lasers for surgical debridement and antimicrobial therapy in the management of peri-implantitis and periodontal therapy. Removal of the noxious foci would naturally promote tissue healing directly. However, there are also anecdotal reports of better healing around routine high-power laser procedures. The precise mechanisms mediating these effects remain to be fully elucidated. This work examines these low-dose laser bystander effects on oral human epithelial and fibroblasts, particularly focusing on the role of human [beta]-defensin 2 (HBD-2 or DEFB4A), a potent factor capable of antimicrobial effects and promoting wound healing. Material and Methods Laser treatments were performed using a near-infrared laser (810 nm diode) at low doses. Normal human oral keratinocytes and fibroblast cells were used and HBD-2 mRNA and protein expression was assessed with real time polymerase chain reaction, western blotting and immunostaining. Role of transforming growth factor (TGF)-[beta]1 signaling in this process was dissected using pathway-specific small molecule inhibitors. Results We observed laser treatments robustly induced HBD-2 expression in an oral fibroblast cell line compared to a keratinocyte cell line. Low-dose laser treatments results in activation of the TGF-[beta]1 pathway that mediated HBD-2 expression. The two arms of TGF-[beta]1 signaling, Smad and non-Smad are involved in laser-mediated HBD-2 expression. Conclusions Laser-activated TGF-[beta]1 signaling and induced expression of HBD-2, both of which are individually capable of promoting healing in tissues adjacent to high-power surgical laser applications. Moreover, the use of low-dose laser therapy itself can provide additional therapeutic benefits for effective clinical management of periodontal or peri-implant disease.